Serum amyloid A and C‐reactive protein positive nodule in alcoholic liver cirrhosis, hard to make definite diagnosis. Issue 5 (22nd May 2013) - Kim, Soo Ryang; Kondo, Fukuo; Otono, Yumi; Imoto, Susumu; Ando, Kenji; Hirakawa, Makoto; Fukuda, Katsumi; Sasaki, Madoka; Kim, Soo Ki; Komaki, Takamitsu; Tsuchida, Shinobu; Kobayashi, Sawako; et al.
<x xml:space="preserve">Abstract</x> We describe a case of serum amyloid A (SAA) and C‐reactive protein (CRP) positive nodule detected by immunohistochemical analysis in a 37‐year‐old woman with alcohol‐related cirrhosis. Imaging studies at first admission pointed to hepatocellular carcinoma (HCC), a dysplastic nodule, an inflammatory pseudotumor or focal nodular hyperplasia (FNH). Ultrasonography‐guided biopsy in Segment 2 showed minimal atypical changes, except for a slight increase in cell density and micronodular cirrhosis in the non‐nodular portion. gadolinium‐ethoxybenzyl‐diethylenetriamine pentaacetic acid‐enhanced magnetic resonance imaging carried out after a year and a half revealed hypervascularity in the arterial phase and isointensity in the hepatobiliary phase. Three years thereafter, however, the imaging displayed a change from isointensity to a defect in the hepatobiliary phase, and the nodule demonstrated minimal histological atypia. Immunohistochemical staining of the nodule was positive for SAA, CRP, liver fatty acid‐binding protein and glutamine synthetase, but negative for β‐catenin, heat shock protein 70 and Glypican 3. Organic anion transporter (OATP)8 staining was weaker in the nodule than in the non‐nodular portion of the alcohol‐related micronodular cirrhosis. The nodule was diagnosed as an SAA and CRP positive nodule, and HCC was ruled out. Despite the change from isointensity to a defect in the hepatobiliary phase, no evidence of HCC was found in the biopsy specimen. The change may be explained more by the weak OATP8 staining compared with that of alcohol‐related liver cirrhosis than by malignant transformation into HCC.